Cranberry polyphenols and agave agavins impact gut immune response and microbiota composition while improving gut barrier function, inflammation, and glucose metabolism in mice fed an obesogenic diet - Medina-Larqué, Ana-Sofía; Rodríguez-Daza, María-Carolina; Roquim, Marcela; Dudonné, Stéphanie; Pilon, Geneviève; Levy, Émile; Marette, André; Roy, Denis; Jacques, Hélène; Desjardins, Yves (Frontiers in Immunology, 2022)
The consumption of plant-based bioactive compounds modulates the gut microbiota and interacts with the innate and adaptive immune responses associated with metabolic disorders. The present study aimed to evaluate the effect of cranberry-polyphenols (CP), rich in flavonoids, and agavins (AG), a highly branched agave-derived neo-fructans, on cardiometabolic response, on the gut microbiota composition, metabolic endotoxemia, and mucosal immunomodulation of C57BL6 male mice fed an obesogenic high-fat and high-sucrose (HFHS) diet for 9 weeks. Interestingly, CP+AG-fed mice had improved glucose homeostasis. Oral supplementation with CP selectively and robustly (5-fold) increases the relative abundance of Akkermansia muciniphila, a beneficial bacteria associated with metabolic health. AG, either alone or combined with CP (CP+AG), mainly stimulated the glycan-degrading bacteria Muribaculum intestinale, Faecalibaculum rodentium, Bacteroides uniformis, and Bacteroides acidifaciens. This increase of glycan-degrading bacteria was consistent with a significantly increased level of butyrate in obese mice receiving AG, as compared to untreated counterparts. CP+AG-supplemented HFHS-fed mice had significantly lower levels of plasma LBP than HFHS-fed controls, suggesting blunted metabolic endotoxemia and improved intestinal barrier function. Gut microbiota and derived metabolites interact with the immunological factors to improve intestinal epithelium barrier function. Oral administration of CP and AG to obese mice contributed to dampen the pro-inflammatory immune response through different signaling pathways. CP and AG, alone or combined, increased toll-like receptor (TLR)-2 (Tlr2) expression, while decreasing expression of interleukin 1ß (ILß1) in obese mice. Moreover, AG selectively promoted the anti-inflammatory marker Foxp3, while CP increased the expression of NOD-like receptor family pyrin domain containing 6 (Nlrp6) inflammasome. The intestinal immune system was also shaped by dietary factors recognition. Indeed, the combination of CP+AG significantly increased the expression of aryl hydrocarbon receptors (Ahr). Altogether, both CP and AG can shape gut microbiota composition and regulate key mucosal markers involved in the repair of the epithelial barrier integrity, thereby attenuating obesity-associated gut dysbiosis, metabolic inflammation and improving glucose homeostasis.